2018
DOI: 10.5294/aqui.2018.18.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Validación del cuestionario CTM-3-modificado sobre satisfacción con la continuidad de cuidados: un estudio de cohortes

Abstract: Objetivos: validar el contenido y constructo de la encuesta CTM-3 (Care Transitions Measure- 3 preguntas) modificada. Determinar el nivel de satisfacción de los usuarios con la continuidad de cuidados de enfermería interniveles y relacionarlo con la presencia de Informe de Cuidados de Enfermería tras su última hospitalización. Material y método: estudio de cohortes retrospectivo, con 131 pacientes hospitalizados en el Complejo Hospitalario de Cartagena (España).La satisfacción con la continuidad de cuidados se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…In the set of 131 patients, made up of a group of exposed, to whom nurses gave a report with data on the planning of nursing care on leaving the hospital and another group of unexposed 8/13 patients, to whom no report was delivered at discharge, found that care report completion slightly influences satisfaction with continuity of care. 15 In these results, we can also infer the effectiveness of the nursing work in discharges, and confirm or refute the nurses' perception regarding their work at nursing discharge. In a bibliographic review carried out in Spain, 16 it is stated that although in the analyzed studies there was no detailed assessment of aspects of the discharge report that make it useful to guarantee continuity of care, it was necessary to establish active communication channels with nursing staff from PHC, to implement improvement measures.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the set of 131 patients, made up of a group of exposed, to whom nurses gave a report with data on the planning of nursing care on leaving the hospital and another group of unexposed 8/13 patients, to whom no report was delivered at discharge, found that care report completion slightly influences satisfaction with continuity of care. 15 In these results, we can also infer the effectiveness of the nursing work in discharges, and confirm or refute the nurses' perception regarding their work at nursing discharge. In a bibliographic review carried out in Spain, 16 it is stated that although in the analyzed studies there was no detailed assessment of aspects of the discharge report that make it useful to guarantee continuity of care, it was necessary to establish active communication channels with nursing staff from PHC, to implement improvement measures.…”
Section: Discussionmentioning
confidence: 54%
“…18 Discharge with protocolized record of poor patient safety facilitates family participation, avoids re-entry and makes the patient's autonomous role visible. 19 However, in the study on user satisfaction in continuity of care, 15 was evaluated positively. When correlating satisfaction with the assistance report, it is shown that it slightly influences the perception of satisfaction in continuity of care.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used CTM-15 or CTM-3 (a simplified version of the instrument) to evaluate care transition have shown high scores, indicating a positive quality in the patients' perception (15)(16) . There is a tendency for participants to answer questions in the affirmative (15,17) , producing positive results that perhaps are distorted and do not represent the true quality of the care transition (18) . Therefore, it is recommended that the CTM be used with caution and associated with other quality of care indicators (17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…The quality of care transition in emergency departments is expected to be lower than in inpatient units due to the accelerated pace of care and the shorter length of stay (5) . The literature indicates a positive association between patient satisfaction, care transition and length of stay (15) . In addition, it is assumed that the professionals' conception of the purpose of their work in emergencies is related to the care of patients with life-threatening conditions, so that perhaps, after clinical stabilization, the patient's transition to home would not be a priority of these services.…”
Section: Discussionmentioning
confidence: 99%
“…15 and Content Validation of the Care Transitions Measure (CTM-3), which allows measuring the satisfaction of patients with the continuity of care. 16 It can be noticed the increase of investigations on the professional competences considering its development, construction of profiles guided by areas of nursing specialties, evaluations based on the expertise of specialists and the validation of the content of instruments used in nursing care.…”
Section: Introductionmentioning
confidence: 99%